Improvisation and System from inside and outside: Steve Coleman’s music through Adorno’s critical philosophy - Carvalho, Frederico Lyra de (Música Popular em Revista, 2021)
In this article we propose to analyse some aspects of the music and musical thought of the musician Steve Coleman through the philosophy of Theodor Adorno. We will deal with Coleman's relationship to tradition and the concept of jazz, the practice of improvisation and the systematicality of his music. These questions will be treated under the prism of the dialectics of identity and non-identity dear to Adorno's Negative Dialectics. The objective is to try to demonstrate some of the contradictions that circumscribe Coleman's work and how it is built through them. We will deal with Coleman's relationship to the jazz tradition, his practice of improvisation and the systematicality of his music.